Is There Such a Thing as Latin America? - Curvale, Carolina; Pérez, Gustavo (Política. Revista de Ciencia Política, 2018)
This paper investigates whether Latin America exists as a region beyond geographical proximity. Claims about the uniqueness of Latin America come in different forms, but a number of them have focused on political institutions. Through the study of models of transition to democracy and to dictatorship, we find no evidence that Latin American countries share crucial unobserved characteristics that influence their transition probabilities. This finding invites to reflect on how we think of regional studies and about the appropriateness of employing standard econometric techniques.